The Young Everest Study: preliminary report of changes in sleep and cerebral blood flow velocity during slow ascent to altitude in unacclimatised children. Issue 5 (7th March 2013) - Gavlak, Johanna C; Stocks, Janet; Laverty, Aidan; Fettes, Emma; Bucks, Romola; Sonnappa, Samatha; Cooper, Janine; Grocott, Michael P; Levett, Denny Z; Martin, Daniel S; Imray, Christopher H; Kirkham, Fenella J
Abstract : Background: Cerebral blood flow velocity (CBFV) and sleep physiology in healthy children exposed to hypoxia and hypocarbia are under-researched. Aim: To investigate associations between sleep variables, daytime end-tidal carbon dioxide (EtCO2 ) and CBFV in children during high-altitude ascent. Methods: Vital signs, overnight cardiorespiratory sleep studies and transcranial Doppler were undertaken in nine children (aged 6–13 years) at low altitude (130 m), and then at moderate (1300 m) and high (3500 m) altitude during a 5-day ascent. Results: Daytime (130 m: 98%; 3500 m: 90%, p=0.004) and mean (130 m: 97%, 1300 m: 94%, 3500: 87%, p=0.0005) and minimum (130 m: 92%, 1300 m: 84%, 3500 m: 79%, p=0.0005) overnight pulse oximetry oxyhaemoglobin saturation decreased, and the number of central apnoeas increased at altitude (130 m: 0.2/h, 1300 m: 1.2/h, 3500 m: 3.5/h, p=0.2), correlating inversely with EtCO2 (R 2 130 m: 0.78; 3500 m: 0.45). Periodic breathing occurred for median (IQR) 0.0 (0; 0.3)% (130 m) and 0.2 (0; 1.2)% (3500 m) of total sleep time. At 3500 m compared with 130 m, there were increases in middle (MCA) (mean (SD) left 29.2 (42.3)%, p=0.053; right 9.9 (12)%, p=0.037) and anterior cerebral (ACA) (left 65.2 (69)%, p=0.024; right 109 (179)%; p=0.025) but not posterior or basilar CBFV. The right MCA CBFV increase at 3500 m was predicted by baseline CBFV and change in daytime SpO2 and EtCO2 at 3500 m (R 2 0.92); these associations were not seen on the left. Conclusions: This preliminary report suggests that sleep physiology is disturbed in children even with slow ascent to altitude. The regional variations in CBFV and their association with hypoxia and hypocapnia require further investigation.